Physiological oxygen tension modulates soluble growth factor profile after crosstalk between chondrocytes and osteoblasts. (3rd February 2016) - Zhang, Tao; Xie, Jing; Sun, Ke; Fu, Na; Deng, Shuwen; Lin, Shiyu; Shi, Sirong; Zhong, Juan; Lin, Yunfeng
Abstract: Objectives: Physiological oxygen tension plays a critical role in homoeostatic maintenance and development of endochondral bone. Based on the proximity between uncalcified cartilage and subchondral bone, and microchannels that serve as a message delivery network between them, we aimed to explore the influence of low oxygen tension on soluble factor secretion in both chondrocytes and osteoblasts, after co‐culture. Materials and methods: Contact co‐culture was achieved for morphological observation using red fluorescent protein (RFP)‐labelled chondrocytes and green fluorescent protein (GFP)‐labelled osteoblasts, and non‐contact co‐culture achieved by transwell chambers. This was used to screen genetic variation of growth factors in hypoxia, including respective phenotypic markers, factors involving hypoxia and angiogenesis relationships, bone morphogenetic family proteins, and other general factors. Results: We observed a significant increase in chondrocyte size following co‐culture, in both normoxia and hypoxia, but not of osteoblasts. Expression of Aggrecan in chondrocytes and alkaline phosphatase in osteoblasts was down‐regulated under hypoxia following co‐culture. Under hypoxia, we found that expression of hypoxia‐inducible factor‐1α, vascular endothelial growth factor‐A/B, VE‐cadherin, bone morphogenetic protein‐2, and insulin‐like growth factor‐1 in chondrocytes, increased, but HIF‐1 α, platelet‐derived growth factor, BMP‐5/‐6 and fibroblast growth factor‐1 in osteoblasts, decreased. Conclusions: These results not only indicate the importance of crosstalk between chondrocytes and osteoblasts but also improve our understanding of the mechanisms underlying homoeostatic maintenance of endochondral bone.